PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR DAN AKTIVITAS PESERTA DIDIK PADA PEMBELAJARAN TEMATIK KELAS V SD NEGERI 1 WAY LAGA - Maharani, Elza (Jurnal Analisis Pendidikan Sosial, 2024)
This research was motivated/encouraged by the low learning outcomes and activity of students in Thematic Learning at fifth-grade students of SD Negeri 1 Way Laga. The aim of this research was to enhance students’ learning outcomes and activity in Thematic Learning by implementing discovery Learning Model. The type of this research was Classroom Action Research (CAR) which carried out in three cycles, with each cycle consisting of planning, implementing, observing, and reflecting. The result showed that (1) the implementation of Discovery Learning Model in Thematic Learning at fifth-grade students of SD Negeri 1 Way Laga could enhance the students’ learning outcomes. It can be seen from the learning outcomes of each cycle. The average value of student learning outcomes in the first cycle was 58.95 with the percentage of completeness was 34.21%. In the second cycle, the average value was 68.68 with the percentage of completeness was 52.63%. Then, there was an enhancement again in the third cycle that the average value was 80.26 with a percentage of completeness is 81.58%. (2) The implementation of the discovery learning model could also enhance the students’ activity. It could be seen from the enhancement of students’ activity in learning based on the results of observations in each cycle. The first cycle was 56.25%, in the second cycle it enhanced by 72.92%, and enhanced in the third cycle by 87.50%.